2019
DOI: 10.1186/s12913-018-3796-0
|View full text |Cite
|
Sign up to set email alerts
|

Extending alcohol brief advice into non-clinical community settings: a qualitative study of experiences and perceptions of delivery staff

Abstract: BackgroundAt a population level, the majority of alcohol-related harm is attributable to drinkers whose consumption exceeds recommended drinking levels, rather than those with severe alcohol dependency. Identification and Brief Advice (IBA) interventions offer a cost-effective approach for reducing this harm. Traditionally, IBA interventions have been delivered in healthcare settings and therefore contextual influences on their use in non-clinical settings are not well understood.MethodsQualitative face-to-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the participants in our study suggested using mobile or web-based self-awareness tools. Such tools are also known to be accepted when implemented in non-clinical settings [ 27 ]. However, it is unclear if this approach also has the same effectiveness compared to presenting self-awareness tools in the GP’s waiting rooms [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the participants in our study suggested using mobile or web-based self-awareness tools. Such tools are also known to be accepted when implemented in non-clinical settings [ 27 ]. However, it is unclear if this approach also has the same effectiveness compared to presenting self-awareness tools in the GP’s waiting rooms [ 27 ].…”
Section: Discussionmentioning
confidence: 99%